Strategi Humas PT Bank Sumut dalam Meningkatkan Citra Positif melalui Media Jurnalistik - Kurnia Balqis, Putri Salwa; Saragih, M. Yoserizal; Abidin, Syahrul (Comit: Communication, Information and Technology Journal, 2024)
The use of the internet by public relations practitioners gives them additional power to carry out their duties, because all digital PR activities can be easily accessed by the public wherever and whenever they want. If we look at modern society which is inseparable from the internet and electronic devices, using the internet is very effective because it gives everyone a new way to fulfill their daily needs. The type of research carried out in this research is qualitative research, namely research based on post-positivist philosophy, used to examine the condition of natural objects. The results of this research show that the public relations strategy in improving the image through journalistic media is publications that carefully carry out public relations activities such as publicity, publications, news, press releases, and maintaining the company's reputation and various internal activities.